Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional dan Kecerdasan Spiritual Terhadap Tingkat Pemahaman Mahasiswa Akuntansi: Studi pada STIE STEKOM (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of intellectual intelligence, emotional intelligence, and spiritual intelligence on the level of accounting comprehension among accounting students at the Modern College of Economics (STEKOM). The population of this study consists of all 60 accounting students at STEKOM, with a sample of 52 respondents selected using purposive sampling and calculated using the Slovin formula. The analytical methods employed include validity testing, reliability testing, multicollinearity testing, heteroscedasticity testing, normality testing, multiple linear regression, t-tests, F-tests, and the coefficient of determination using IBM SPSS Statistics 2025 software. The results indicate that all research instruments were valid and reliable. The multiple linear regression test revealed that intellectual intelligence, emotional intelligence, and spiritual intelligence each have a positive and significant influence on the level of accounting comprehension, with significance values below 0.05. Simultaneously, these three independent variables also significantly affect accounting comprehension, with an R² value of 0.612, meaning that 61.2% of the variation in accounting comprehension levels can be explained by these three variables. This study concludes that students' intellectual, emotional, and spiritual aspects play a crucial role in enhancing accounting comprehension. Therefore, a holistic academic development approach should be implemented to support optimal learning outcomes in the field of accounting